Soft tissue extensor mechanism tendon ruptures of the knee. (2021) - Rhind, John-Henry; Lancaster, Patrick; Ahmed, Usman; Carmont, Michael
Abstract : Ruptures of the extensor mechanism of the knee are serious injuries requiring prompt diagnosis and treatment. They can be divided into soft tissue and bony causes. Soft tissue tendon injuries can be either partial or complete. Rupture of the quadriceps tendon is an uncommon injury and is more frequent in patients over the age of 40 years. Patella tendon ruptures are even rarer and are more frequent in patients under the age of 40 years. Causes can be direct or indirect. Complete ruptures of the quadriceps tendon or patella tendon benefit from early surgical management, while partial ruptures may be managed non-operatively. This article gives an overview of the presentation, assessment and management of soft tissue extensor mechanism tendon ruptures for core surgical, acute care common stem and emergency medicine trainees.